Economic Considerations of Acute Pain Medicine Programs. Issue 4 (December 2017) - Gray, Chancellor F.; Smith, Cameron R.; Zasimovich, Yury; Tighe, Patrick J.
Abstract : Acute pain medicine (APM) services influence many different aspects of postoperative recovery and function. Here, we discuss the various stakeholders of an APM service, review the direct and indirect impact on said stakeholders, review the shared and competing interests between APM programs and various payer systems, and discuss how APM services can help service lines align with the interests of the recent Centers for Medicare and Medicaid Services Innovations Comprehensive Care for Joint Replacement Model.